The effect of electronic games in shaping culture among children- Field study on students of Ahmed Bolsan Elementary School in Tiaret State - Ghemmaz, Zakaria; Ben Labbaad , Elghali (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This study aims to reveal the effect of electronic games on shaping culture in children. It was carried out on a sample of primary school students, Ahmed Bollesnan, in the municipality of Mahdia, in the state of Tiaret. and in this study, we tried to answer the following main question, what is the effect of electronic games on the formation of culture in children through the study sample. Two sub-questions were included within this question: -Do war and fighting games cause the child to be aggressive? -Does electronic games addiction lead to withdrawal from social activities? In addition to defining the objectives of the study, the most important of which is to identify the impact that electronic games have on the child, and we have adopted the descriptive approach because we saw that it was the most appropriate and used the questionnaire in the interview as a tool to collect data due to the nature of the respondents who were represented in thirty individuals, males and females, who are students of the year section The fourth elementary school is in Ahmed Boulsnan School, and the sample was deliberately chosen. and the most important results of the study are electronic games that gain the child an aggressive behavior Excessive use of electronic games leads to the child's withdrawal from social activities